Characterization and gas exchange in accessions of Saccharum complex under salinity in the Sub-middle São Francisco, Brazil - Welson L. Simões; Anderson R. de Oliveira; Jucicléia S. da Silva; Vinicius G. Torres Junior; Weslley O. da Silva; Lizz K. de Morais (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Salinity is one of the factors that most limit agricultural yield in the Brazilian semi-arid region. In this context, the present study aimed to evaluate the leaf gas exchange and biometric characteristics of accessions of the Saccharum complex subjected to salt stress. The experiment was carried out in a greenhouse, installed at Embrapa Semiárido, in Petrolina, PE, Brazil. The experimental design was in randomized blocks, with the treatments represented by 19 accessions belonging to different genera/species, being 10 accessions of Saccharum officinarum (BGCN 6, BGCN 91, BGCN 104, BGCN 127, BCGN 90, BGCN 101, BGCN 102, BGCN 118, BGCN 125 and BGCN 122), two accessions of Saccharum spp. (BGCN 87 and BGCN 89), one accession of Saccharum hybridum (BGCN 88), one accession of Saccharum robustum (BGCN 94), four accessions of Erianthus arundinaceus (BGCN 117, BGCN 119, BGCN 120 and BGCN 123) and one accession of Miscanthus spp., with three repetitions. Biometric characteristics, chlorophyll index and leaf gas exchange of the accessions were evaluated when they were subjected to irrigation with salinized water (6.0 dS m-1). E. arundinaceus accessions (BGCN 120 and BGCN 123) showed the highest photosynthetic rate, transpiration rate, plant height and leaf length, indicating greater adaptability to salt stress and could be promising in breeding programs.